MANAGEMENT OF PANGLUKATAN BEJI SELATI AS A SPIRITUAL TOURISM ATTRACTION IN BUNUTIN TRADITIONAL VILLAGE, BANGLI DISTRICT - I Komang Wartamana; I Ketut Arta Widana; I Nengah Alit Nuriawan; Ida Ayu Tary Puspa; I Putu Suyasa Ariputra (Ride: Journal of Cultural Tourism and Religious Studies, 2025)
Panglukatan Beji Selati is one of the spiritual tourism attractions located in Bunutin Traditional Village, Bangli District, Bangli Regency. This place is known as a melukat and metamba location that has spiritual value and traditional medicine through the use of red soil. Its existence offers tranquility and spiritual experience in a sacred natural atmosphere. However, the management of this tourist attraction is still not optimal in terms of facilities, promotion, and management participation. The purpose of this study was to determine the potential of Panglukatan Beji Selati and its management and implications as a spiritual tourism attraction. This study uses a qualitative descriptive analysis method with the theory of 6A tourism components, tourism management theory, and tourism impact theory. Data were obtained through observation, interviews, literature studies, and documentation. The results of the study indicate that Panglukatan Beji Selati has the potential as a spiritual tourism attraction that includes attractions, activities, accessibility, facilities, additional services, and tour packages. Management is carried out independently by the Banjar Adat Selati community, Bunutin Traditional Village, but has not been maximized due to limited human resources and inadequate facilities.